Some new fractional Hermite-Hadamard type inequalities for functions with co-ordinated extended (s, m)-prequasiinvex mixed partial derivatives - Saleh, Wedad; Lakhdari, Abdelghani; Kilicman, Adem; Frioui, Assia; Meftah, Badreddine (Elsevier, 2023)
This article introduces extended ð Þ s; m -prequasiinvex functions on coordinates, a new form of generalized convex function. Using a previously established identity, we derive new fractional Hermite-Hadamard type integral inequalities for functions whose mixed partial derivatives belong to this new class of functions. The obtained results generalize existing Hermite-Hadamard type inequalities and have numerous applications in mathematics and physics. To demonstrate the utility of our findings, we provide examples of applications to special means, such as arithmetic, harmonic and p-logarithmic means.